PENGARUH TEKNIK SELF CONTROL TERHADAP PERILAKU KECANDUAN GAME ONLINE SISWA DI SMK MUHAMMADIYAH 2 PEKANBARU - Annisa, Usdiatul; Yakub, Elni; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of self control techniques on online game addiction behavior of students of Pekanbaru Muhammadiyah II Vocational School. This type of research is a quantitative research with Pre-Experiment method. The research design used in this study is